Clinical profile and recovery pattern of dysphagia in the COVID-19 patient: A prospective observational cohort within NSW. Issue 2 (March 2023) - Clayton, Nicola A.; Walker, Elizabeth; Freeman–Sanderson, Amy
Abstract: Background: The impact of COVID-19 on swallowing function is not well understood. Despite low hospital admission rates in Australia, the virus and subsequent treatment affects swallow function in those requiring intensive care unit (ICU) treatment. As such, the current pandemic provides a unique opportunity to describe swallowing function and outline dysphagia characteristics and trajectory of recovery for a series of cases across NSW. Aim: The aims of this study were to describe (i) physiological characteristics of swallowing dysfunction and (ii) pattern of swallowing recovery and outcomes, in ICU patients with COVID-19. Methods: All patients admitted to 17 participating NSW Health ICU sites over a 12-month period (March 2020–March 2021), diagnosed with COVID-19, treated with the aim for survival, and seen by a speech pathologist for clinical swallowing examination during hospital admission were considered for inclusion. Demographic, critical care airway management, speech pathology treatment, and swallowing outcome data were collected. Results: Twenty-seven patients (22 male; 5 female) with a median age of 65 years (interquartile range [IQR] = 15.5) were recruited. All required mechanical ventilation. Almost 90% of the total cohort had pre-existing comorbidities, with the two most frequently observed being diabetes (63%, 95% confidence interval = 44%–78%) and cardiac disease (59%, 95% confidence interval = 40%–75%) in origin. Prevalence of dysphagia was 93%, with the majority (44%) exhibiting profound dysphagia at the initial assessment. Median duration to initiate oral feeding was 38.5 days (IQR = 31.25) from ICU admission, and 33% received dysphagia rehabilitation. Dysphagia recovery was observed in 81% with a median duration of 44 days (IQR = 29). Positive linear associations were identified between duration of intubation, mechanical ventilation, hospital and ICU length of stay, and the duration to speech pathology assessment (p < 0.005), dysphagia severity (p < 0.002), commencing oral intake (p < 0.02), dysphagia recovery (p < 0.004), and enteral feeding (p < 0.024). Conclusion: COVID-19 considerably impacted swallowing function in the current study. Although many patients recovered within an acceptable timeframe, some experienced persistent severe dysphagia and a protracted recovery with dependence on enteral nutrition.